Urgensi Kamar Barokah Jemaah Haji: Kebijakan Hak Sipil dan Implementasi Akomodasi Syariah - Rangkuti, HM Affan; Bahri, Syamsul (IAIN Langsa, 2025)
Ideally, the organization of Hajj as a comprehensive act of worship should include the fulfillment of pilgrims' fundamental rights, including the biological needs of legally married couples. However, in reality, facilities that accommodate these needs, such as Kamar Barokah, have not yet been incorporated into official policies for Hajj accommodation services. This study aims to analyze the urgency of Kamar Barokah as a civil right for Hajj pilgrims and its implementation within the framework of syariah accommodation. This article falls under library research with a qualitative approach. The methodology used is policy research, presented in a descriptive-analytical narrative. The findings indicate that Kamar Barokah is an urgent necessity that must be systematically facilitated to maintain the biological, emotional, and psychological well-being of pilgrims throughout their pilgrimage. Therefore, the state, through the Ministry of Religious Affairs, needs to formulate regulations that integrate this service into Hajj accommodation contracts and ensure proper dissemination of information during the manasik (pre-Hajj guidance) phase to optimize its implementation in alignment with syariah accommodation principles.